Microstructural and Radioluminescence Characteristics of Nd3+ Doped Columbite-Type SrNb2O6 Phosphor - EKMEKÇİ, METE KAAN (SPRINGER/PLENUM PUBLISHERS, 2017)
Undoped and different concentration Nd3+ doped SrNb2O6 powders with columbite structure were synthesized by molten salt process using a mixture of strontium nitrate and niobium (V) oxide and NaCl-KCl salt mixture as a flux under relatively low calcining temperature. X-ray diffraction analysis results indicated that SrNb2O6 phases found to be orthorhombic columbite single phase for undoped, 0.5 and 3 mol% Nd3+ doping concentrations. Phase composition of the powders was examined by SEM-EDS analyses. Radioluminescence properties of Nd3+ doped samples from UV to near-IR spectral region were studied. The emissions increased with the doping concentration of up to 3 mol%, and then decreased due to concentration quenching effect. There is a sharp emission peak around 880 nm associated with F-4(5/2) -> I-4(9/2) transition in the Nd3+ ion between 300 and 1100 nm. The broad emission band intensity was observed from 400 to 650 nm where the peak intensities increased by increasing Nd3+ doping concentration. All the measurements were taken under the room temperature.
Keywords: Strontium metaniobate; Molten salt synthesis; Radioluminescence; CRYSTAL-GROWTH; LUMINESCENCE; NIOBATE; PHOTOLUMINESCENCE